Advances in advertising research. Vol. VII : bridging the gap between advertising academia and practice - Christodoulides, George; Stathopoulou, Anastasia; Eisend, Martin (Springer Gabler ; European Advertising Academy, 2017)
"Focusing on a range of advertising formats, this book provides international state-of-the-art research inter alia on the fast evolving and increasingly complex advertising landscape that raises a number of challenges for advertisers. Further research is needed to guide choices regarding ad content and execution, media placement, social networks, and campaign effectiveness. Advances in Advertising Research are published by the European Advertising Academy (EAA). This volume is a selective collection of research presented at the 14th International Conference in Advertising (ICORIA), which was held in London (UK) in July 2015. The conference gathered more than 150 participants from various countries from nearly all continents, including Europe, North and South America, Asia, and Australia"--Publisher's description.
Keywords: Advertising -- Research.; elektronické knihy; electronic books